Ac-SDKP attenuates ER stress-stimulated collagen production in cardiac fibroblasts by inhibiting CHOP-mediated NF-κB expression - Suhail, Hamid; Peng, Hongmei; Matrougui, Khalid; Rhaleb, Nour-Eddine (Frontiers in Pharmacology, 2024)
Inflammation and cardiac fibrosis are prevalent pathophysiologic conditions associated with hypertension, cardiac remodeling, and heart failure. Endoplasmic reticulum (ER) stress triggers the cells to activate unfolded protein responses (UPRs) and upregulate the ER stress chaperon, enzymes, and downstream transcription factors to restore normal ER function. The mechanisms that link ER stress-induced UPRs upregulation and NF-κB activation that results in cardiac inflammation and collagen production remain elusive. N-Acetyl-Ser-Asp-Lys-Pro (Ac-SDKP), a natural tetrapeptide that negatively regulates inflammation and fibrosis, has been reported.Whether it can inhibit ER stress-induced collagen production in cardiac fibroblasts remains unclear. Thus, we hypothesized that Ac-SDKP attenuates ER stress-stimulated collagen production in cardiac fibroblasts by inhibiting CHOP-mediated NF-κB expression. We aimed to study whether Ac-SDKP inhibits tunicamycin (TM)-induced ER stress signaling, NF-κB signaling, the release of inflammatory cytokine interleukin-6, and collagen production in human cardiac fibroblasts (HCFs). HCFs were pre-treated with Ac-SDKP (10 nM) and then stimulated with TM (0.25 µg/mL). We found that Ac-SDKP inhibits TM-induced collagen production by attenuating ER stress-induced UPRs upregulation and CHOP/NF-κB transcriptional signaling pathways. CHOP deletion by specific shRNA maintains the inhibitory effect of Ac-SDKP on NF-κB and type-1 collagen (Col-1) expression at both protein and mRNA levels. Attenuating ER stress-induced UPR sensor signaling by Ac-SDKP seems a promising therapeutic strategy to combat detrimental cardiac inflammation and fibrosis.